Participatory Forest and Agriculture Land Use Planning, Allocation and Management at Village Level - Department of Agricultural Land Management (Department of Agricultural Land Management, 2018)
The main objectives of this Manual on Participatory Forest and Agriculture Land Use Planning, Allocation and Management (PFALUPAM Manual) are to: To encourage the participation and ownership in the implementation of activities related to the governance and management of natural forest resources and agricultural land use that provided maximum benefits to livelihood development by creating fixed occupation for local villagers; To facilitate the government technical officers of all levels, especially at local level (province, district, clusters) and the village administration authorities including all ethnicity villagers for taking full responsible and common agreement on the implementation PFALUPAM approach in order to develop local livelihood occupation and upgrade the living condition standard of the rural families towards the development of socio-economic, along with the protection of environment according to local landscapes situation; To develop an accurate and precise data-base, maps and plan on Forest and Agriculture Land Use Management Zone (FLUMZ Plan) that consisted with reality of local situation and provide for all stakeholders to use it as evidence-base into the development of policies, strategies, programs, investment plan and socio-economic development. The Manual was co-authored by Rathana Peou and Joost Vervoort from CCAFS.